Integrating early refresher practice in height safety and rescue training. (December 2018) - Lawani, Kenneth; Hare, Billy; Cameron, Iain
Highlights: Height safety and rescue skills decay within four weeks after acquisition. Technicians will struggle to sustain skill performances up to three months without any practice. Knowledge can potentially be retained longer than skills over a three month period. Devices mostly used for rescue and evacuation do not have task steps that are cued. Abstract: The non-routine practice of wind turbine height safety and rescue skills after training has significant impact on the competency and health and safety of construction and maintenance technicians. The proposition is that wind technicians who undertake initial training without practically carrying out hands-on rescue roles are most likely to forget the procedural steps during emergencies except there is an early refresher practice integrated within the system. Longitudinal study of 30 (subsample) wind technicians using Job Knowledge Test (JKT), hands-on practice test with Situational Judgment Test (SJT) and pictograph of the rescue device was employed. While the level of performance of wind technicians improved during acquisition, there was observed decline in performances over one and three month non-practice intervals. This confirms the significance of integrating early refresher practice of rescue and evacuation skills and the factors influencing the competence of the technicians over these timescale. To improve the competency of technicians and reduce the risk of injury or failed rescue, actual timescales have been identified showing that early refresher practice should be undertaken at three months after acquisition for returning technicians and within one month for new technicians.